Quality by design for a vaccine release immunoassay: a case study. (October 2013) - Yarovoi, Helen; Frey, Tina; Bouaraphan, Silikhone; Retzlaff, Mary; Verch, Thorsten
Background: As quality by design (QbD) for pharmaceutical product development is being expanded to include analytical methods, we applied QbD to the development of antigenicity assays measuring in vitro relative potency of a quadrivalent vaccine candidate.Results: After establishing development targets together with customers, immunoassays were developed to meet objectives. Statistical design of experiments was used to optimize method parameters and establish a design space. Systematic risk analysis enabled identification of potential risks to method performance that were mitigated by investigating the available design space around risk factors and by establishing appropriate control strategies.Conclusion: We found QbD-based method development was a more efficient and systematic approach that could also potentially facilitate assay transfers and life cycle management.